Public administrations on TikTok. Communication, narrative, and frequency of publication of the profiles of the ministries of Spain - Alonso-López, Nadia (2024)
The interest of public administrations in interacting and generating conversation with citizens has led to the opening of profiles on social networks. The present work analyzes how the General Administration of the State, in particular, the ministries of the Government of Spain, are using the TikTok network to communicate with citizens, what content they are publishing, what the format and tone of their publications is, and what frequency of publication they maintain, to know how institutional communication of the ministries is on this social network and observe if they follow a strategic use of their profiles. To do this, a quantitative content analysis of the publications of the profiles of the 7 ministries with active presence on TikTok has been carried out, from the first publication of each profile studied until March 31, 2023. For the analysis, different variables have been considered which collect the figures of the profiles, the tone of the publications, and the structure and format of the contents. The results show that the ministries maintain a low publication frequency, and there is a disparity in the type of tone used or intention of their publications and in the formats, which suggests a lack of common communication strategy by the Government of Spain to maximize performance on this social network.